2010
DOI: 10.1002/syn.20814
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine causes deficits in radial migration and alters the distribution of glutamate and GABA neurons in the developing rat cerebral cortex

Abstract: Prenatal cocaine exposure induces cytoarchitectural changes in the embryonic neocortex; however, the biological mechanisms and type of cortical neurons involved in these changes are not known. Previously we found that neural progenitor proliferation in the neocortical ventricular zone (VZ) is inhibited by cocaine; here we examine the changes in cortical neurogenesis and migration of glutamate and GABA neurons induced by prenatal cocaine exposure. Pregnant rats received 20 mg/ kg of cocaine intraperitoneally tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 76 publications
(102 reference statements)
1
35
1
Order By: Relevance
“…Kosofsky, on the other hand, has studied prenatal cocaine in a dose-response fashion in the mouse and found long term effects on cocaine reward that can be summarized as increasing the sensitivity to cocaine assessed by operant behavior and reducing the sensitivity to cocaine measured with classical conditioning such as CPP (Rocha et al 2002; Malanga et al 2007). These findings can be interpreted as selective effects of prenatal cocaine on descending cortical projections perhaps mediated by altered neural development in cerebral cortex (Lee et al 2011). …”
mentioning
confidence: 99%
“…Kosofsky, on the other hand, has studied prenatal cocaine in a dose-response fashion in the mouse and found long term effects on cocaine reward that can be summarized as increasing the sensitivity to cocaine assessed by operant behavior and reducing the sensitivity to cocaine measured with classical conditioning such as CPP (Rocha et al 2002; Malanga et al 2007). These findings can be interpreted as selective effects of prenatal cocaine on descending cortical projections perhaps mediated by altered neural development in cerebral cortex (Lee et al 2011). …”
mentioning
confidence: 99%
“…Consistent with these primate studies, during periods of early neocorticogenesis in rodents, defined by mitotically active neural progenitor cells in the ventricular zone (VZ), cocaine inhibits growth of the neocortex and disrupts the distribution of glutamate and GABAergic neurons [18] .…”
Section: Research Highlightmentioning
confidence: 68%
“…In nonhuman primates, it has been shown that prenatal COC administration resulted initially in a decrease in cell production within the fetal pseudostratified ventricular epithelium, which was then followed by an increase in neurogenesis (Lidow and Song, 2001). Lee et al (2011) suggested that COC may inhibit neuronal differentiation during cortical neurogenesis and the migration of glutamate and γ-aminobutyric acid (GABA) neurons, alterations that could potentially explain language delays and motor-development impairments.…”
Section: Dendritic Cell Architecturementioning
confidence: 99%
“…Prenatal COC exposure affects various neurotransmitters, including 5-HT, DA, NE, and glutamate (Henderson et al, 1991;Keller and SnyderKeller, 2000;Lee et al, 2011).…”
Section: Neurotransmitter Alterationsmentioning
confidence: 99%